The way past winter - Hargrave, Kiran Millwood, 1990-; O'Hara, Lauren (Chronicle Books, 2020)
Mila lives with her sisters, Pipa and Sanna, her brother Oskar, and their sled dogs in the forest where winter has held sway for five years, ever since their father disappeared; but now a strange scary man, flanked by twelve young boys, seems to have bewitched Oskar and taken him away--and Mila, convinced her brother is in danger, leads her sisters in a desperate journey across the frozen wild-lands to find their brother, and perhaps a way past an eternal winter.